Pengaruh Rebusan Daun Kersen Terhadap Kadar Glukosa Darah Penderita Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Bontobahari - Edison Siringoringo; Asri; Safruddin (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2021)
Diabetes mellitus is one of the biggest health problems in the world. Diabetes mellitus or what is commonly called diabetes (diabetes) is a disease that causes the patient’s body to be unable to control the level of sugar (glycose) in the blood. At this time, many people are doing treatment by using plants as traditional medicine. One of them is cherry leaves. Kersen leaves are believed to reduce blood glucose levels in type II diabetes mellitus sufferers. The purpose of this study was to determine the effect of Kersen leaf decoction on blood glucose levels in patients with Type II diabetes in the Bontobahari Community Health Center in 2021. The research design used in this study was a quantitative research design with a true-experimental method (pure experiment) with a pre-post design. Test control group design. The sample used was 38 respondents, with a sampling technique that is probability sampling with simple random sampling. Analysis of the data in this study using the Unpaired T test statistical test. The results of the analysis using the unpaired T-test statistical test obtained p-value = 0.000 (p ≤ 0.05), which means that Ho is rejected and Ha is accepted. There is an effect of Kersen Leaf Decoction on Blood Glucose levels in people with Type II Diabetes in the Bontobahari Community Health Center Work Area. 2021.